Pasting and leaching properties of irradiated starches from various botanical sources - Mohd Adzahan, Noranizan; Mat Hashim, Dzulkifly; Syed Muhammad, Sharifah Kharidah; Abdul Rahman, Russly; Ghazali, Zulkafli; Hashim, Kamaruddin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
Changes to the physicochemical properties of wheat, sago and tapioca starches subjected to gamma ray, electron beam and microwave irradiations and the conditions that lead to wheat starch having leaching behaviour similar to sago or tapioca starch were studied. The properties were characterised through swelling and leaching behaviours of the starch granules and retrogradation following pasting. The leaching of wheat starch increased tremendously and resulted in amylose to amylopectin ratios in the leachate similar to that of native sago and tapioca starches. This observation is significant as wheat starch is known to have a leachate composition of mostly amylose. This opens up the possibility of utilising wheat starch in snacks where tapioca and sago starch are commonly used. It was observed that the required conditions for such changes were exposure to microwave for 8 and 10 minutes, electron beam at 5 and 10 kGy and gamma ray at 5 kGy.